Morocco : Ex Post Evaluation of Exceptional Access Under the 2012 Precautionary and Liquidity Line Arrangement. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Morocco's Ex Post Evaluation of Exceptional Access Under the 2012 Precautionary and Liquidity Line (PLL) Arrangement. The Ex Post Evaluation confirms that the 2012-14 PLL arrangement was consistent with the PLL qualification standards and requirements under the exceptional access policy at the time of the PLL arrangement request in August 2012 and at the subsequent reviews. The authorities' policies helped maintain macroeconomic stability and reduce fiscal and external vulnerabilities, despite unfavorable external developments. It is observed that despite the significant macroeconomic achievements under the 2012-14 PLL arrangement, a number of policy challenges remained to be fully addressed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Morocco